2022
DOI: 10.3389/fonc.2022.925379
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Potential of Dietary Nanonutraceuticals for Prostate Cancer: An Extensive Review

Abstract: There are more than two hundred fifty different types of cancers, that are diagnosed around the world. Prostate cancer is one of the suspicious type of cancer spreading very fast around the world, it is reported that in 2018, 29430 patients died of prostate cancer in the United State of America (USA), and hence it is expected that one out of nine men diagnosed with this severe disease during their lives. Medical science has identified cancer at several stages and indicated genes mutations involved in the cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 295 publications
(218 reference statements)
0
1
0
Order By: Relevance
“…Despite their distinct characteristics, both EVs and RNA nanoparticles share a common objective: achieving efficient and specific delivery of therapeutic agents. In addition, a diverse range of technologies exists for delivering therapeutics tailored to various disease applications. This highlights the diverse approaches being explored to advance drug delivery and therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their distinct characteristics, both EVs and RNA nanoparticles share a common objective: achieving efficient and specific delivery of therapeutic agents. In addition, a diverse range of technologies exists for delivering therapeutics tailored to various disease applications. This highlights the diverse approaches being explored to advance drug delivery and therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, several researchers have demonstrated that some nutraceuticals can counteract tumor development and progression by targeting the cancerous cells at multiple levels, such as by promoting cell cycle arrest or apoptosis, suppressing metastasis, invasion, angiogenesis, and by modifying the redox status and the tumor microenvironment Furthermore, some natural bioactive compounds are able to resensitize drug-resistant tumors via their pleiotropic capability to affect different intra-cellular pathways [8]. Interestingly, a recent extensive review by Hitesh Chopra et al described the main experimental evidence demonstrating the effectiveness of nanonutraceutical approaches in the management of prostate cancer, highlighting that nutraceuticals could represent a promising therapeutic tool in prostate cancer therapy [9].…”
Section: Introductionmentioning
confidence: 99%